PENEGAKAN HUKUM PELANGGARAN HAK CIPTA KARYA MUSIK DALAM BENTUK KASET BERDASARKAN UNDANG – UNDANG REPUBLIK INDONESIA NOMOR 19 TAHUN 2002 TENTANG HAK CIPTA - Indrawan, Ida Bagus; Rai Asmara Putra, Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Seeing the rampant piracy of musical works in the form of tapes, would make the existence of Act - Act Nomor 19 of 2002 regarding Copyright questionable. Turns Act - the Act has not been able to solve the problems of the offense - would be copyright infringement, including the rampant piracy tapes. It takes a sinkronanisasi between agencies - agencies authorized to enforce the law in the field of copyright. Not only from the police, prosecutors, government, musician, and the seller, but the role of the wider community are needed to enforce existing laws. If the buyer is reduced, then the stock will be pirated tapes will also be reduced.Besides, it also needs to be revised back to the Law Nomor 19 Year 2002 regarding Copyright by inserting a provision that has not been there before. As it is intended to guarantee legal certainty and provide better legal protection to the creators of musical works (songs) in Indonesia. In addition, public education needs that these activities had violated the Copyright Act. If the law enforcement community about Copyright in running as it should and is firm, this will reduce the level of piracy in paspearan tapes and people will be afraid to engage in unlawful copying.
Keywords: piracy, copyright musical works